Strategi Pembinaan Adab Siswa Kelas IX Oleh Guru Akidah Akhlak di MTS Al-Hidayah Patumbak - Suci Dahlya Narpila; Windu Asmoro; Bagus Irvan Embriana; Nugraha Pratama Ramadhan (CV. Lenggogeni Data Publishing, 2025)
The aim of writing this article is to (1) Identify the moral condition of class IX students at MTS Al-Hidayah Patumbak, (2) Analyze the supporting and inhibiting factors for developing the morals of class IX students at MTS Al-Hidayah Patumbak, and (3) Describe the strategies of aqidah teachers morals in developing the manners of class IX students at MTS Al-Hidayah Patumbak. The type of research method used is qualitative research, with descriptive analysis techniques proposed by Miles and Huberman which include interviews, observation and documentation. The subjects of this research are (1) Madrasah Head Teacher, (2) Aqidah Akhlak Teacher, and (3) Counseling Guidance (BK) Teacher at MTS Al-Hidayah Patumbak located on Jl. Pelita No.75, Patumbak Village, Medan, North Sumatra. The results of this research indicate that the current moral condition of class IX MTS Al-Hidayah Patumbak students requires efforts to ensure maximum moral development of students. Supporting and inhibiting factors for developing the morals of class IX students at MTS Al-Hidayah Patumbak, include: Supporting Factors: (1) Increasing religious values, social values and exemplary, (2) The role of the madrasa head, (3) A good school environment, ( 4) Collaboration from all parties in the school, and (5) school policies to develop student morals. Inhibiting Factors: (1) Limited time to improve students' morals, (2) Living environment, (3) Low awareness of students regarding the importance of developing manners in schools, and (4) advances in the times such as the emergence of advanced technologies such as cellphones and so on. others that influence students' moral development. And the moral aqidah teacher's strategy in developing the manners of class IX students at MTS Al-Hidayah Patumbak, namely: (1) Implementing an example, (2) Giving warnings, (3) Giving punishment, and (4) Class conditioning. Abstrak Penulisan artikel ini bertujuan untuk (1) Mengidentifikasi bagaimana kondisi akhlak siswa kelas IX di MTS Al-Hidayah Patumbak, (2) Menganalisis faktor pendukung dan penghambat pembinaan akhlak siswa kelas IX di MTS Al-Hidayah Patumbak, dan (3) Mendeskripsikan strategi guru akidah akhlak dalam membina adab siswa kelas IX di MTS Al-Hidayah Patumbak. Jenis metode penelitian yang digunakan ialah penelitian kualitatif, dengan teknik analisis deskriptif yang dikemukakan oleh Miles dan Huberman yang meliputi wawancara, observasi, dan dokumentasi. Adapun subjek penelitian ini adalah (1) Guru Kepala Madrasah, (2) Guru Akidah Akhlak, dan (3) Guru Bimbingan Konseling (BK) MTS Al-Hidayah Patumbak yang berlokasi di Jl. Pelita No.75, Patumbak Kampung, Medan, Sumatera Utara. Hasil penelitian ini menunjukkan bahwa kondisi akhlak siswa kelas IX MTS Al-Hidayah Patumbak saat ini memerlukan perlu adanya upaya untuk menjamin pembinaan akhlak peserta didik secara maksimal. Faktor pendukung dan penghambat pembinaan akhlak siswa kelas IX di MTS Al-Hidayah Patumbak, meliputi: Faktor Pendukung: (1) Meningkatkan nilai keagamaan, nilai sosial, dan keteladanan, (2) Peran kepala madrasah, (3) Lingkungan sekolah yang baik, (4) Kolaborasi dari semua pihak di sekolah, dan (5) kebijakan sekolah untuk mengembangkan moral siswa. Faktor Penghambat: (1) Terbatasnya waktu untuk meningkatkan akhlak siswa, (2) Lingkungan tempat tinggal, (3) Rendahnya kesadran siswa akan pentingnya pembinaan adab di sekolah, dan (4)kemajuan zaman seperti munculnya teknologi-teknologi canggih seperti handphone dan lain-lain yang memengaruhi perkembangan moral siswa. Dan strategi guru akidah akhlak dalam membina adab siswa kelas IX di MTS Al-Hidayah Patumbak, yaitu: (1) Penerapan keteladanan, (2) Pemberian teguran, (3) Pemberian hukuman, dan (4) Pengkondisian kelas. Kata kunci: Strategi Guru, Pembinaan Adab, Akidah Akhlak